Synthetic Studies towards the Total Synthesis of Providencin - Schweizer, Eliane; Gaich, Tanja; Brecker, Lothar; Mulzer, Johann (My University, 2007)
A synthetic approach to assemble the uncommon furylcyclobutane substructure in providencin has been developed starting from a commercially available cyclobutane precursor.
Keywords: 540